PENANAMAN NILAI ANTIKORUPSI SISWA SD MELALUI PENDIDIKAN KELUARGA DI KAMPUNG PRENGGAN - Waskito, M Nur; Pambudi, Dholina Inang (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2018)
The habit of corruption that is entrenched if since elementary school age is not strengthened by the planting of character and leadership spirit to reject corruption. The act of corruption is a set of activities that deviate and harm others. This study aims to determine the anti-corruption value planting and to know the supporting and inhibiting factors of the anti-corruption value of elementary school students through family education in Prenggan Village. This study uses qualitative research. Informants that are used as subjects are parents of elementary school students, heads of RW / RT, elementary school students, and village heads and objects of family education research. The Methods of collecting data on interviews, observation and documentation. This study uses a credibility test by triangulating techniques and source triangulation. The results of this study indicate that Planting the Anti-Corruption Value of Elementary School Students through Family Education in Prenggan Village, Planting anti-corruption values through exemplary, habituation, dialogue on planting religious values in Prenggan Village starts from the family and local community's commitment to bring up behaviors that reflect anti-corruption attitudes such as being honest , always be disciplined and build a relationship of mutual trust with the community. The supporting factors for the planting of anti-corruption values of elementary school students through family education in Kampung Prenggan family environment, peer groups, family education in the planting of anti-corruption values. While the inhibiting factor is awareness of children in understanding corruption.